Alexander Hamilton, young statesman - Higgins, Helen Boyd (Young patriots series, 2008)
Provides a fictional account of the childhood of the man who would become the first Secretary of the Treasury, as he enjoys peaceful days with his books and pet parrot on Caribbean islands, dreaming of one day attending college in the American Colonies.